2014
DOI: 10.1007/s13762-014-0635-7
|View full text |Cite
|
Sign up to set email alerts
|

Latitude-dependent underestimation of microbial extracellular enzyme activity in soils

Abstract: Decomposition of soil organic matter by microorganisms is a major process governing the carbon balance between soil and atmosphere which needs to be fully understood. Extracellular enzyme activity is often the limiting factor for microbial utilization of soil organic matter. Contrary to expectations, we observed that enzymatic activity rises at increasing temperatures in soils and sediments. Current climatic change will induce the increase of global mean temperatures, frequency of extreme heat events and soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 34 publications
1
66
0
Order By: Relevance
“…Santana et al (2015) proposed a thermophilic C dissimilatory organic‐S mineralization characteristic pathway for the release of SO $ _4^{2 - } $ and NH ­­ $ _4^+ $ depending on the decomposition of proteinaceous substrates. The temperatures, considered to be necessary for these thermophiles to provide significant activity, have been shown to be highly frequent at medium and low latitudes ( Gonzalez et al, 2015) and during daily cycles ( Portillo et al, 2012); for instance, temperature measurements during summer days showed values > 40°C in topsoils from S Spain for more than 10 h a day ( Portillo et al, 2012). This high temperature niche observed in soils offers these thermophiles their own window of opportunity to develop a significant role in the terrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…Santana et al (2015) proposed a thermophilic C dissimilatory organic‐S mineralization characteristic pathway for the release of SO $ _4^{2 - } $ and NH ­­ $ _4^+ $ depending on the decomposition of proteinaceous substrates. The temperatures, considered to be necessary for these thermophiles to provide significant activity, have been shown to be highly frequent at medium and low latitudes ( Gonzalez et al, 2015) and during daily cycles ( Portillo et al, 2012); for instance, temperature measurements during summer days showed values > 40°C in topsoils from S Spain for more than 10 h a day ( Portillo et al, 2012). This high temperature niche observed in soils offers these thermophiles their own window of opportunity to develop a significant role in the terrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is highly limited information on how water availability rules the activity of microorganisms and their enzymes in soils (Biederman et al, 2016;Moxley et al, 2019). Temperatures for the incubation of the enzyme assays were selected to represent soil conditions and common natural ranges for the extracellular enzyme activity from mesophilic (Fierer, Colman, Schimel, & Jackson, 2006;Townsend, Vitousek, & Holland, 1992) and thermophilic (Gonzalez et al, 2015) microorganisms and looking for facilitating the discrimination between mesophiles and thermophiles in the EEA assays. For instance, 20°C represented a minimum surface soil temperature during the summer season at the Southern Spain sampling sites whereas 60°C was a commonly reached summer temperature at the soil surface at these sites and was generally the optimum growth temperature for reported soil thermophiles (Marchant, Banat, Rahman, & Berzano, 2002;Portillo et al, 2012).…”
mentioning
confidence: 99%
“…Besides, this procedure avoids the previous ambiguity to quantify the decay rate over an asymptotic EEA decay curve (Renella et al, 2007) and greatly reduces the incubation time required to complete an EEA decay estimation from about 30 days (Renella et al, 2007) can frequently get hot (Gonzalez et al, 2015;Portillo et al, 2012;Santana & Gonzalez, 2015) and so these thermophilic enzymes could perform optimally in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially important role for soil thermophiles has been shown to recycle organic C, N, and S (Portillo et al, 2012;Santana & Gonzalez, 2015;Santana, Portillo, González, & Clara, 2013). Gonzalez et al (2015) demonstrated the existence of peaks of maximum EEA at high temperatures in all soils tested from different latitudes. This suggested that the elevated high-temperature EEA might be a consequence of the activity being carried out by soil thermophilic microorganisms.…”
mentioning
confidence: 87%
See 1 more Smart Citation